Pengaruh Orientasi Kewirausahaan dan Orientasi Pasar Terhadap Keunggulan Bersaing UMKM Digital Printing di Padang Bulan Medan - Jesica Eninta Sinulingga; Wan Rizca Amelia; Hery Syahrial (Universitas Medan Area, 2022)
This study purposed to determine the Effect of Entrepreneurship Orientation and Market Orientation on the Competitive Advantage of Digital Printing MSME in Padang Bulan Medan. This type of research is associative with a quantitative approach. The population in this study were 102 digital printing businesman using the slovin formula, so the number of samples in this study was 51 respondents. Analysis of the data used is the test of validity, reliability, classical assumption test, multiple linear regression, partial and simultaneous hypothesis testing, and the coefficient of determination with the help of the IBM SPSS Statistics 25 program. The results show that partially there is a positive and significant influence of entrepreneurial orientation on competitive advantage and there is a positive and significant influence of market orientation on competitive advantage; while simultaneously there is a positive and significant influence of entrepreneurial orientation and market orientation on competitive advantage. The value of Adjusted R Square (R2) is 0.588 or 58.8%. This value shows Competitive Advantage can be explained by the Entrepreneurial Orientation and Market Orientation variables of 58.8%. The remaining 41.2% can be explained by other variables that were not studied in this study.